PENGARUH RELATIONSHIP MARKETING TERHADAP CUSTOMER RETENTION PADA STUDIO MUSIK 58 SURAKARTA - Indah Handaruwati; Obed Christian Wibowo (Entrepreneurship Faculty, Universitas Garut, 2020)
Abstract– This study aims to analyze the effect of Relationship Marketing on Customer Retention in 58 Surakarta music studios. In connection with this problem, the following hypothesis is proposed, H1: Allegedly there is the influence of Customer Experience on Customer Retention, H2: Allegedly there is an influence of Communication on Customer Retention, H3: Allegedly there is the influence of Conflict Handling on Customer Retention, H4: Allegedly there is the influence of Customer Experience, Communication, Conflict Handling simultaneously for Customer Retention. The population in this study were all customers of Surakarta 58 studio music studio rental services, sampling using purposive sampling and convenience sampling techniques. The samples used in this study were 80 consumers. Data collection using a questionnaire. Data analysis was performed with multiple linear regression analysis test with SPSS 16.00 software. The results showed that Customer Experience had no significant effect on Customer Retention with a significance value of 0.142, Communication had a significant effect on Customer Retention with a significance value of 0.045, Conflict Handling had a significant effect on Customer Retention with a significant value of 0,000, Customer Experience, Communication and Conflict Handling had a significant effect Simultaneous to Customer Retention of 27,691. Abstrak– Penelitian ini bertujuan untuk menganalisis pengaruh Relationship Marketing terhadap Customer Retention pada studio musik 58 Surakarta. Sehubungan dengan masalah tersebut, diajukan hipotesis sebagai berikut, H1 : Diduga ada pengaruh Customer Experience terhadap Customer Retention, H2: Diduga ada pengaruh Communication terhadap Customer Retention, H3: Diduga ada pengaruh Conflict Handling terhadap Customer Retention, H4: Diduga ada pengaruh Customer Experience, Communication, Conflict Handling secara simultan terhadap Customer Retention. Populasi dalam penelitian ini adalah semua pelanggan pengguna jasa sewa studio musik 58 Surakarta, pengambilan sampel menggunakan teknik purposive sampling dan convenience sampling.Sampel yang digunakan dalam penelitian ini sebanyak 80 responden.Pengumpulan data menggunakan kuesioner.Analisis data dilakukan dengan uji analisis regresi linear berganda dengan software SPSS 16.00. Hasil penelitian menunjukan bahwa Customer Experience tidak berpengaruh secara signifikan terhadap Customer Retention dengan nilai signifikansi 0.142, Communication berpengaruh signifikan terhadap Customer Retention dengan nilai signifikansi 0.045, Conflict Handling berpengaruh signifikan terhadap Customer Retention dengan nilai signifikan 0.000, Customer Experience, Communication dan Conflict Handling berpengaruh secara simultan terhadap Customer Retention sebesar 27.691.